Pengaruh Leverage, Good Corporate Governance, dan Pertumbuhan Laba terhadap Kualitas Laba Perusahaan yang Terindeks Jakarta Islamic Indeks di Bursa Efek Indonesia - Sululing, Siswadi (MUI Kota Pekanbaru, 2023)
This research is entitled Analysis Leverage, Good Corporate Governance (GCG), and Profit Quality on Earnings Quality in Companies listed on the Indonesia Stock Exchange (IDX) and indexed by the Jakarta Islamic Index (JII). This research was conducted because the previous research was mostly conducted on companies listed on the Indonesia Stock Exchange, while only a few were conducted on companies indexed by the Jakarta Islamic Index so that research was very open, by adding variables namely profit quality and earnings quality. The purpose of this study was to determine the direct effect on earnings quality in companies indexed by the Jakarta Islamic Index.The population of this study are companies listed and indexed by the Jakarta Islamic Index on the Indonesia Stock Exchange, while the samples used are financial reports for 2018-2020. The sampling method was carried out using purposive sampling method. The number of samples obtained was 90 company data listed on the Indonesia Stock Exchange and indexed by the Jakarta Islamic Index (30 companies and an observation period of 3 years, namely 2018-2020). The data analysis method used by the author is multiple linear regression analysis method both partially and simultaneously using SPSS 23. The results showed that partially leverage has a significant effect on earnings quality, good corporate governance has a significant effect on earnings quality and earnings quality has a significant effect on earnings quality, while simultaneously showing that leverage, good corporate governance, and earnings quality have a significant effect on earnings quality.